Etnosains sebagai Sumber Kontekstual dalam Pendidikan Demokrasi pada Pembelajaran PPKn Tematik SD (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
This study aims to explore the potential of ethnoscience as a contextual source in democratic education in thematic PPKn learning in elementary schools. Ethnoscience, as a representation of local knowledge that develops in the culture of society, can be used as a meaningful, relevant, and contextual learning medium for students. In the context of democratic education, values such as deliberation, mutual cooperation, and social justice contained in ethnoscience practices make a significant contribution to strengthening students' democratic character and understanding. The method used in this study is descriptive qualitative with a literature study approach. The results of the study indicate that the integration of ethnoscience in thematic PPKn learning can increase student involvement, strengthen cultural identity, and foster democratic awareness and participation from an early age. Thus, the use of ethnoscience as a contextual source not only enriches teaching materials,but also becomes a strategic means of instilling democratic values that are in accordance with the local context of students.